Evaluation of teaching performance in public educational institutions - Alvarez-Andrade, Guiliana Tessy Estrella (2020)
The purpose of this research is to identify significant differences regarding the evaluation of teacher performance between participants and non-participants of the Second Specialty Program in Primary Education Didactics in those in public educational institutions belonging to UGEL No. 01, year 2019, is of comparative descriptive level, whose design is non-experimental and of a transversal nature, ex post facto. For this, a class observation sheet was designed, a data collection instrument, which was made up of 26 single response items on a Likert scale, its design was made taking into account the Good Teacher Performance Framework (MBDD) . The intentional non-probabilistic sample consisted of 72 teachers of the primary level in public institutions, belonging to UGEL No. 01 of Metropolitan Lima, Peru. The results found show significant differences in teacher performance in both groups compared. It also shows that there are differences between the two domains: a) Preparation for student learning, and, b) Teaching for student learning.